1987
DOI: 10.1002/jor.1100050120
|View full text |Cite
|
Sign up to set email alerts
|

The use of laser doppler flowmetry to evaluate anterior cruciate blood flow

Abstract: The purpose of this study was to quantitate the blood flow of the anterior cruciate ligament in vivo. Functional flow was evaluated using laser Doppler flowmetry (LDF), for which the output signal, blood cell flux (BCF), is expressed in terms of volts. Ten patients undergoing routine arthroscopic surgery with clinically intact anterior cruciate ligaments were selected at random for participation in the study. Under arthroscopic visualization, a 2.2-mm probe was placed through a trocar sleeve into the anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…[2][3][4]16,24,25,28 LDF depends on the doppler shift occurring when monochromatic light is scattered by moving blood cells. Studies by Astrom confirmed that this technology can be used to study blood flow in human Achilles' tendon.…”
mentioning
confidence: 99%
“…[2][3][4]16,24,25,28 LDF depends on the doppler shift occurring when monochromatic light is scattered by moving blood cells. Studies by Astrom confirmed that this technology can be used to study blood flow in human Achilles' tendon.…”
mentioning
confidence: 99%
“…temporary ischemia have been inadequately studied because of the nature of microsphere estimations; a limit of six data points are available and these must be separated by minutes to allow collection of reference organ blood (18,19). Similarly, clearance of bone-seeking isotopes is hampered by a n even more restricted number of data points (5).Laser Doppler flowmetry (LDF) has been utilized extensively in our laboratory over the past 5 years as a method for studying bone, ligament, and meniscus perfusion (12,13,(15)(16)(17)(18). Recently, we documented the reproducibility of LDF in an in vitro bone perfusion chamber (1,10,1 I).…”
mentioning
confidence: 99%
“…Swiontkowski et al [13] used LDF to measure the blood flow in bone and meniscus. Schlehr et al [12] and Pässler et al [11] also used LDF to evaluate the ACL blood flow. They stated that it may be used to assess the viability of anterior substitutes used in various reconstructive procedures without sacrificing ligamentous integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, laser Doppler flowmetry (LDF) has been used to measure the blood flow within capillary beds and has proven to be useful in the clinical and experimental evaluation of blood flow in skin, ligament, and bone [8,[10][11][12][13][14]. The purpose of this study was to evaluate the usefulness of LDF in direct in vivo measurement of the reconstructed ACL's blood flow in the human knee.…”
mentioning
confidence: 99%